Gender and Communal Trait Differences in the Relations Among Social Behaviour, Affect Arousal, and Cardiac Autonomic Control - D’Antono, Bianca; Moskowitz, D. S.; Miners, Christopher; Archambault, Jennifer (Journal of behavioral medicine, 2005)
To examine the relation between social behaviour and vagal activity, the communal behaviour of healthy college men (N = 33) and women (N = 33) was manipulated while monitoring heart rate (HR) and respiratory sinus arrhythmia (RSA). The subjects were classified as low or high on communal trait. Communal behaviour was manipulated by having the subjects behave in an agreeable or quarrelsome manner in scripted role-plays. HR, RSA and self-report arousal were obtained during or immediately following baseline, experimental and relaxation periods. 2 (Gender) x 2 (Communal Trait; low/high) x 2 (Condition; agreeable/quarrelsome) ANCOVAs were performed. Men had lower RSA values when behaving in a quarrelsome fashion than agreeable and lower RSA values than women in the quarrelsome condition. In the latter condition, low communal men reported more arousal than other groups. Strong but opposite associations between RSA and affect arousal were observed in low communal men and woman. Men, especially more quarrelsome (less communal) men exhibited weaker vagal control during arousing social situations.